Heuristic and Hermeneutic Readings of Maher Zain’s “Ramadan”: A Riffaterrean Semiotic Analysis - Albi Majdi Syam; Akmaliyah Akmaliyah; Yadi Mardiansyah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
‘Ramadhan (Arabic Version)’ to uncover the spiritual and connotative meanings hidden within them. Given that Arabic pop song lyrics are currently a popular means of intellectual communication among Gen Z, Michael Riffaterre's semiotic analysis, with its concepts of double reading, hypogram, matrix, and variant, was chosen as the methodological approach. This qualitative descriptive study used observation and note-taking techniques and literature study, with song lyrics as the main object. The results of the analysis show that heuristic (literal) reading produces separate denotative meanings, such as in the phrase فَالشّوقُ طَال (longing has been long). However, the presence of ungrammatical elements such as the personification of Ramadan as لِلرُّوحِ دَوَاء (‘medicine for the soul’) forces the reader towards the hermeneutic (retroactive) stage. Hermeneutic reading reveals the core Matrix of the lyrics, namely Longing for Ramadan, which is transformed through the Model of a call (munada) full of love ( يَا حَبِيب). Variants such as يَا نُورُ الْهِلاَلْ and يَا شَهرَ القُرآن serve to reinforce this Matrix. This song uses the hypogram of piety (QS. Al-Baqarah: 197) and ends with a prayer that reflects the resolution of the poetic tension between the desire for eternity and the transience of time. This study confirms the effectiveness of Riffaterre's model in exploring spiritual and symbolic values in contemporary Arabic music.